Direct Biodiesel Production from Wet Microalgae Biomass of Chlorella pyrenoidosa through In Situ Transesterification. (29th September 2013) - Cao, Hechun; Zhang, Zhiling; Wu, Xuwen; Miao, Xiaoling
Abstract : A one-step process was applied to directly converting wet oil-bearing microalgae biomass of Chlorella pyrenoidosa containing about 90% of water into biodiesel. In order to investigate the effects of water content on biodiesel production, distilled water was added to dried microalgae biomass to form wet biomass used to produce biodiesel. The results showed that at lower temperature of 90°C, water had a negative effect on biodiesel production. The biodiesel yield decreased from 91.4% to 10.3% as water content increased from 0% to 90%. Higher temperature could compensate the negative effect. When temperature reached 150°C, there was no negative effect, and biodiesel yield was over 100%. Based on the above research, wet microalgae biomass was directly applied to biodiesel production, and the optimal conditions were investigated. Under the optimal conditions of 100 mg dry weight equivalent wet microalgae biomass, 4 mL methanol, 8 mL n-hexane, 0.5 M H2 SO4, 120°C, and 180 min reaction time, the biodiesel yield reached as high as 92.5% and the FAME content was 93.2%. The results suggested that biodiesel could be effectively produced directly from wet microalgae biomass and this effort may offer the benefits of energy requirements for biodiesel production.